2020
DOI: 10.15536/thema.v17.2020.619-643.1324
|View full text |Cite
|
Sign up to set email alerts
|

Análise de possíveis influenciadores do nível de Proficiência Científica de egressos do Ensino Médio ao interpretar a Física do Trânsito

Abstract: Todos fazemos parte do trânsito, seja na função de condutor, passageiro, seja na de pedestre. Esse tema é rico em situações que podem ser analisadas sob a ótica da Física. Compreender as relações entre Física e Trânsito, além de possuir um grande potencial problematizador dentro do Ensino de Física, pode levar a desenvolver nos cidadãos uma cultura de cuidado e responsabilidade. Além disso, por ser um contexto presente no cotidiano da maioria, acredita-se que a temática possa servir de meio para verificar se o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 2 publications
0
5
0
3
Order By: Relevance
“…Of those that applied the TBSL and its versions, all revealed that the best results were identified in the subtest of the science content knowledge. At the same time, the worst were evidenced in the subtest of the nature of science by Sousa (2019b), Nascimento-Schulze et al (2006), Özdem et al (2010), Rivas et al (2017), Vizzotto and Mackedanz (2018) and on the subtest of the impact of science and technology on society by Coppi and Sousa (2019a), Lima and Garcia (2015), Vizzotto (2019) and Vizzotto and Del Pino (2020a). Camargo et al (2011) found that first-year students and teachers scored worse on the nature of science subtest, while for final-year students this occurred on both subtests.…”
Section: Study Results: Performance On the Dimensions Of Scientific L...mentioning
confidence: 99%
See 4 more Smart Citations
“…Of those that applied the TBSL and its versions, all revealed that the best results were identified in the subtest of the science content knowledge. At the same time, the worst were evidenced in the subtest of the nature of science by Sousa (2019b), Nascimento-Schulze et al (2006), Özdem et al (2010), Rivas et al (2017), Vizzotto and Mackedanz (2018) and on the subtest of the impact of science and technology on society by Coppi and Sousa (2019a), Lima and Garcia (2015), Vizzotto (2019) and Vizzotto and Del Pino (2020a). Camargo et al (2011) found that first-year students and teachers scored worse on the nature of science subtest, while for final-year students this occurred on both subtests.…”
Section: Study Results: Performance On the Dimensions Of Scientific L...mentioning
confidence: 99%
“…Among the 18 studies that adopted the TBSL and its versions-TACB, TACB-S, TACB-R, and adapted -, Camargo et al (2011), Gresczysczyn et al (2018), Laugksch and Spargo (1996a), Lima and Garcia (2015), Oliveira and Silva-Forsberg (2012), Rivas et al (2017), Vizzotto andDel Pino (2020a, 2020b), and Vizzotto and Mackedanz (2018) revealed that most of the students assessed are scientifically literate. The studies of Sousa (2019a, 2019b), Laugksch and Spargo (1999), Lima and Garcia (2013), Nascimento-Schulze (2006), Vizzotto (2019), and Vizzotto et al (2020, on the other hand, revealed that the majority of the students assessed did not reach the minimum number of hits required to be considered scientifically literate. The research of Özdem et al (2010) showed moderate scientific literacy scores of the investigated students, while that of Nascimento-Schulze et al (2006) indicated that there is a relationship between satisfactory performances on the TACB-R and high interest in scientific topics, as well as good grades and school attendance.…”
Section: Study Results: Performance In Scientific Literacy Assessmentmentioning
confidence: 99%
See 3 more Smart Citations